Propagation of whistler mode waves in Earth’s inner magnetosphere in the presence of field aligned irregularities and geomagnetic curvature - Khatun-E-Zannat, Raahima; Harid, Vijay; Golkowski, Mark; Agapitov, Oleksiy; Hosseini, Poorya (Frontiers in Astronomy and Space Sciences, 2025)
Whistler mode waves are known to propagate in the Earth’s magnetosphere along complex trajectories and have a significant impact on space weather processes and radiation belt energy dynamics. Most past work on propagation trajectories of whistler mode waves has been done using ray tracing, which is appropriate for smoothly varying background plasma densities. Recent spacecraft observations suggest that the cold plasma density in the magnetosphere can often be highly inhomogeneous. In this study, we investigate the propagation of whistler mode waves in cold, inhomogeneous plasma, with a focus on the combined effects of geomagnetic curvature and density irregularities known as magnetospheric ducts. Using both a comprehensive full wave model and a ray tracing model, we simulate wave behavior under conditions representative of Van Allen Probe observations. The presence of magnetospheric ducts produces a more complex wave behavior in the full wave model, leading to a strong spatial modulation, efficient confinement and the formation of shadow region as a result of geomagnetic curvature. The ray tracing simulation provides a complementary perspective, highlighting the propagation paths of individual rays in the background cold plasma density and, demonstrates the reflection, bending and guiding of rays due to density gradients. Employing both of these models provides insight into the effects of density ducts in the whistler mode wave propagation and understanding of the wave power distribution in global magnetospheric models.